(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
An investigation into the aquifer system of the crystalline rocks within Jos and environments was carried out. The area covered some selected sites from the northern senatorial zone down to southern senatorial zone of the state. The geology of each site was study to establish the grain size, texture and geological structures associated with each of the rock type. The rock types in the area are: migmatites, gneisess, granites, and basalts. Vertical electrical sounding (VES) using the Schlumberger full electrode spread was adopted for the geophysical investigation. The spread ranged from 95m-215m. the software IX1D Package developed by Interpex Limited was used for plotting data and iteration of the curves. Thereafter drilling of favourable sites were carried out as the clients could afford at that time using PAT DRILL 301, 401, and Indian Motor Rigs. The VES curves showed that the basement rocks are characterized by A, KHA and KHK curves types. Most of the VES points have four geoelectric layers whose apparent resistivities range from 19Ω -344Ω. The younger granites are characterized by H and HA curves of which the H curves dominate. Here, the geoelectric layer and the apparent reistitvies range from 4-5 and 21 Ω -834Ω respectively. Within the basement complex, drilling revealed that the aquifers are located mainly within the basement rocks, while within the younger granites, they are located at the contact between the regolith and the crystalline rocks and also within the crystalline rocks as fractures. In terms of drillabiblity, the aquifers within the crystalline rocks have low drillability than the unfractured or fresh rocks. Whereas within the regolith, the aquifers have high drillability than the non aquiferious clay. Drilling also showed that coarse grain rocks are more aquiferious than fine grain rocks when weathered. From the investigations, the chances of getting groundwater is higher within the basement complex than the younger granites as the basement complex are more deformed and altered.